The Determinants Of Economic Growth In North African Countries (Efficient: Indonesian Journal of Development Economics, 2023)
Economic growth is one of the most important indicators used in developing and evaluating the economic activity of developing countries, including North African countries, but economic growth faces several major economic challenges such as FDI, unemployment rate, inflation and exchange rate. This study used quantitative research, and data were collected by documentation method with secondary data since 2001-2020, Based on the results of the analysis by panel data regression, it was found that FDI is statistically significant, while it has a positive sign, which indicates that it has a positive impact on economic growth, If FDI increase by1%, economic growth will increase by 0.684%, and there is no impact of inflation and unemployment rate on economic growth, and the exchange rate has a positive and significant impact on economic growth, as each increase leads by 1% in the exchange rate to a increase in economic growth by 0.420%, in future research other variables affecting economic growth, such as the volume of exports, import tariffs, taxes or government regulations.